Criminal Justice News (2015)
Dr. Laura Agnich Receives University Award for Excellence in Contributions to Service Dr. Bryan Miller works with Chatham County Sheriff’s Office Dr. Laurie Gould Accepts issue editor for The CUR Quarterly Dr. Adam Bossler and Graduate Student Justin Hoyle Complete Funded Evaluation Dr. Adam Bossler submitted National Science Foundation Final Report Department Attends Annual Southern Criminal Justice Association (SCJA) Conference Graduate Student Jack Lightfoot and Undergraduate Roland Turner Win Conference Award